If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 2) = -6(x + 5) Reorder the terms: 8(2 + x) = -6(x + 5) (2 * 8 + x * 8) = -6(x + 5) (16 + 8x) = -6(x + 5) Reorder the terms: 16 + 8x = -6(5 + x) 16 + 8x = (5 * -6 + x * -6) 16 + 8x = (-30 + -6x) Solving 16 + 8x = -30 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 16 + 8x + 6x = -30 + -6x + 6x Combine like terms: 8x + 6x = 14x 16 + 14x = -30 + -6x + 6x Combine like terms: -6x + 6x = 0 16 + 14x = -30 + 0 16 + 14x = -30 Add '-16' to each side of the equation. 16 + -16 + 14x = -30 + -16 Combine like terms: 16 + -16 = 0 0 + 14x = -30 + -16 14x = -30 + -16 Combine like terms: -30 + -16 = -46 14x = -46 Divide each side by '14'. x = -3.285714286 Simplifying x = -3.285714286
| (2x+9)(4x+2)= | | 15m+3m=-18 | | 12y=3(4y-7) | | 10b-9b=2 | | 4-2(3X-2)=2(X-3) | | 8v+12=4(2v+3) | | 2+x*3+2x=21 | | 8x^2+-14x+3=0 | | 1.3p+1=1.6 | | 3x-2x+1=5 | | 62=x-6x+2 | | 7=1x(3+2x) | | -8+4x+4x=-88 | | 2(4x-3)-7(x+1)= | | 10+12x=3(5+3x)-3 | | 175=175-2.75n | | 7y+8=32 | | (0.3x-55)=180 | | (x-10)-0.15(x-10)=50 | | 7x+2y+14=0 | | -8+4x+4x=-8 | | J=7+-3t | | 2x^2+-250x+5000=0 | | -9=2v+9-5v+6 | | 1440=(x-2)*180 | | J=7t+-3t | | 4(x-7)-10=2 | | 2cos(x)+1=0.5 | | 5x^2+28x+-12=0 | | 6+6x=-60 | | 1.25g=15g+.50 | | y=2(1)+2.50(1) |